New Contributions to the Ericion umbellatae Alliance in the Central Iberian Peninsula - Piñar Fuentes, José (2021)
The study of heathlands dominated by Erica australis, E. umbellata and Cistus populifolius in the centre and west of the Iberian Peninsula allows us to separate the eight shrubland communities. The taxonomic analysis of E. australis distinguishes two subspecies: E. australis subsp. australis and E. australis subsp. aragonensis. The statistical treatment confirms the differences between the subal liances Ericenion aragonensis and Ericenion umbellatae. This ecological, bioclimatic, biogeographical and floristic study has allowed us to differentiate three new associations from the remaining five: TCp = Teucrio oxylepis-Cistetum populifolii nova. HEau = Halimio ocymoidis-Ericetum australis nova. DEu = Drosophyllo lusitanicae-Ericetum umbellatae nova. ECp = Erico australis-Cistetum populifolii Ri vas Goday 1964. PCp = Polygalo microphyllae-Cistetum populifolii Rivas Goday 1964. HEa = Halimio ocymoidis-Ericetum aragonensis Rivas-Martínez 1979. HEu = Halimio ocymoidis-Ericetum umbellatae Rivas Goday 1964. UEu = Ulici eriocladi-Ericetum umbellatae.